Telaah Pemahaman Maqasid Al-Syariah dalam Fatwa Ulama Kontemporer Terkait Nikah Misyar - Multazam, Umar (AHKAM, 2025)
Misyar marriage is a controversial phenomenon among contemporary ulama due to its implications for women's rights and welfare. In this practice, women may relinquish their rights, such as financial support and housing, raising questions about the validity and relevance of misyar marriage within Islamic law. This study aims to analyze the debate among contemporary ulama regarding misyar marriage, focusing on their stance and the fatwas issued based on the maqasid al-syariah perspective. This phenomenon has caused social unrest, particularly in Indonesia, where the practice of misyar marriage has sparked significant discussions among Islamic scholars.The primary point of contention revolves around the maqasid al-syariah principles in misyar marriage, which serve as the main basis for differing scholarly opinions on its legitimacy and relevance in the Islamic legal framework. This study seeks to address two key questions: (1) What is the foundation of contemporary ulama's stance on misyar marriage? (2) How do contemporary ulama's fatwas on misyar marriage align with maqasid al-syariah? Using a qualitative approach, this research employs literature-based analysis, including content and critical analysis of fatwas concerning maqasid al-syariah.The findings indicate two main groups among contemporary ulama: one that permits misyar marriage, represented by Yusuf al-Qardhawi and Wahbah Zuhaili, and another that prohibits it, including 'Abd al-'Aziz bin al-Baz and 'Umar Sulaiman al-Asqar. The fatwas from both perspectives evaluate misyar marriage through the lens of maqasid al-syariah, weighing the balance between its benefits and drawbacks. The implications of this research are highly significant in understanding and applying Islamic law in a way that aligns with contemporary social developments.